A method for calculating the efficiency of photothermal conversion
By setting up a double-sided adhesive sample chamber in a transparent and closed container with a combination of slides and coverslips, micro-diluted the photothermal agent and irradiated the photothermal agent particles with 1064nm laser, combined with the LogNormal model fitting data, the photothermal conversion efficiency is calculated, and the existing photothermal conversion efficiency testing method is solved, and the accurate measurement of photothermal particles and high-precision photothermal conversion efficiency evaluation is achieved.
Patent Information
- Application Number
- CN202211595715.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-12
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-12
AI Technical Summary
The existing photothermal conversion efficiency testing methods have the problem of inaccurate measurement results, mainly due to external factors such as the container status and solution configuration process.
A micro-photothermal conversion efficiency calculation method is adopted. By setting up a double-sided adhesive sample chamber in a transparent and closed container composed of a glass slide and coverslip, micro-diluting the photothermal agent and irradiating the photothermal agent particles with 1064nm laser, timing and shooting the bubble growth process, and fitting the data in the LogNormal model, the photothermal conversion efficiency is calculated.
Accurate photothermal conversion efficiency measurement of photothermal agent particles is achieved, which reduces interference from external factors, improves measurement accuracy, and saves photothermal agent samples and reduces costs.
Smart Images

Figure CN115824973B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photothermal materials, and in particular to a method for testing and calculating trace photothermal conversion efficiency. Background Art
[0002] Photothermal agents are special materials that can absorb specific wavelengths and convert light energy into heat energy, thereby achieving local heating in the area where the photothermal agent is located. In recent years, photothermal therapy and point-like structure heat generation have been widely used in the field of clinical tumor treatment. With the development of technology in recent years, inorganic photothermal agents have more advantages than organic materials, such as ferroferric oxide nanoparticles (Fe 3 O 4 ) is one of the most widely used photothermal agents at present. In the research on photothermal agents, how to use photothermal materials with high photothermal conversion efficiency to convert light energy into heat energy locally is the key issue of this technology. It can be seen that the photothermal conversion performance of the photothermal agent is the basis of the application effect of the photothermal agent, so the accurate determination of the photothermal conversion performance of the photothermal agent is very important. In the current photothermal conversion efficiency test process, it mainly relies on local illumination of the photothermal agent solution and determines the photothermal conversion performance based on the light energy loss before and after illumination. The calculation results are relatively rough and easily affected by external factors such as the container state and the solution configuration process, resulting in inaccurate measurement results and affecting the evaluation of the photothermal agent performance. Summary of the invention
[0003] In view of this, the present invention provides a method for testing and calculating trace photothermal conversion efficiency. Compared with the traditional method for measuring photothermal conversion efficiency of a large number of samples, the photothermal conversion efficiency of local photothermal agent particles is accurately measured, and the measurement results are more accurate.
[0004] The present invention provides a method for calculating the micro-photothermal conversion efficiency test, which mainly includes the following steps:
[0005] Step S1: placing a light-transmitting double-sided adhesive tape in a transparent sealed container composed of a glass slide and a cover glass to serve as a light-transmitting sample chamber;
[0006] Step S2: Disperse the photothermal agent into pure water for micro dilution, and drop the resulting solution onto the double-sided tape in the sample chamber, and wait for it to dry naturally at room temperature for later use;
[0007] Step S3: Fill the sample chamber with pure water, use a laser with a wavelength of 1064nm to irradiate the photothermal agent particles on the surface of the double-sided adhesive tape until bubbles are generated, start timing when the bubbles begin to be generated, and take microscopic photos of the photothermal agent particles and the bubble growth process;
[0008] Step S4: Calculate the apparent photothermal conversion efficiency f during the bubble growth process based on the image data collected during shooting and the calculated water temperature change. Use the LogNormal model to fit the apparent photothermal conversion efficiency f during the bubble growth process with the bubble diameter x data to obtain a fitted data image. According to the fitted data image, the relationship between the photothermal conversion efficiency y and the bubble diameter x is obtained, where:
[0009] The water temperature rise value ΔT satisfies the following formula:
[0010]
[0011] In formula (1), T is the absolute temperature, T 0 is the absolute room temperature, x is the bubble diameter (i.e., twice the distance from the bubble edge to the particle center), C w is the thermal conductivity of water, P abs heat generated for the particles;
[0012] The apparent photothermal conversion efficiency f satisfies the following formula:
[0013]
[0014] In formula (2), c w is the specific heat capacity of water, m w is the mass of the heated water, ΔT is the water temperature rise, P l Power consumption for laser;
[0015] Under ideal conditions, the laser energy is completely absorbed by the photothermal agent particles, then P l =P abs , substituting ΔT into equation (2) to obtain the relationship between the apparent photosothermal conversion efficiency f and the bubble diameter x:
[0016]
[0017] The LogNormal model is used to fit the apparent photothermal conversion efficiency f and the bubble diameter x data satisfying formula (3) to obtain the fitted data image. According to the fitted data image, it is concluded that the relationship between the photothermal conversion efficiency y and the bubble diameter x satisfies the following formula:
[0018]
[0019] In formula (4), y 0 is the starting point of the fitted image, w is the logarithmic standard deviation, x c is the center point of the fitting image, A is the integral area of the fitting image, and x is the bubble diameter.
[0020] An embodiment of the present invention is that the sample chamber includes a porous silicone pad and glass plates respectively covering the through holes at both ends of the porous silicone pad, double-sided tape is coated on the glass plate, and the glass plate does not absorb the 1064nm laser.
[0021] In one embodiment of the present invention, the photothermal agent particles are ferroferric oxide particles, and the particle size range is 1.8-3.0 μm.
[0022] An implementation manner of the present invention is that the laser power ranges from 0.1 to 0.3W.
[0023] An embodiment of the present invention is that the laser source for irradiating the photothermal agent particles is optical tweezers.
[0024] The technical effects of the present invention are:
[0025] The present application uses optical tweezers heating technology to accurately test and calculate the photothermal conversion efficiency of a single, several or a small pile of photothermal agent particles. Compared with the existing methods that mostly use photothermal agent solutions to test the photothermal conversion efficiency, the measurement of a small number of particles in this method can avoid interference from external factors such as environmental factors, achieve in-situ testing in a liquid environment, effectively ensure test accuracy, and require fewer photothermal agent samples, which is more cost-effective, providing a new technical idea for accurately measuring the photothermal conversion efficiency of photothermal agents. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below.
[0027] Figure 1 It is a schematic diagram of the structure of the sample chamber composed of a porous silica gel pad in the present invention;
[0028] Figure 2 This is a diagram of the bubble growth process of ferroferric oxide particles with a particle size of 1.86 μm in the present invention;
[0029] Figure 3 This is a diagram of the bubble growth process of ferroferric oxide particles with a particle size of 2.25 μm in the present invention;
[0030] Figure 4 This is a diagram of the bubble growth process of the ferroferric oxide particles with a particle size of 2.52 μm in the present invention;
[0031] Figure 5 This is a diagram of the bubble growth process of the ferroferric oxide particles with a particle size of 2.90 μm in the present invention;
[0032] Figure 6 This is a fitting curve diagram of the photothermal efficiency data of ferroferric oxide particles with a particle size of 1.86 μm in the present invention;
[0033] Figure 7 This is a fitting curve diagram of the photothermal efficiency data of ferroferric oxide particles with a particle size of 2.25 μm in the present invention;
[0034] Figure 8 This is a fitting curve diagram of the photothermal efficiency data of ferroferric oxide particles with a particle size of 2.52 μm in the present invention;
[0035] Fig. 9 This is a fitting curve diagram of the photothermal efficiency data of ferroferric oxide particles with a particle size of 2.90 μm in the present invention. DETAILED DESCRIPTION
[0036] The present invention will be further described in detail below in conjunction with the embodiments and drawings.
[0037] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. The described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Step S1: a light-transmitting double-sided adhesive tape is placed in a transparent sealed container composed of a glass slide and a cover glass to serve as a light-transmitting sample chamber.
[0039] The function of the sample chamber is to contain the photothermal agent particles and fix the photothermal agent on the double-sided adhesive layer in the sample chamber. At the same time, it is necessary to allow external light sources to enter the sample chamber to heat the photothermal agent and photograph the process. The backing material of the photothermal agent should not produce additional absorption of the external light source. Therefore, see Figure 1 The sample chamber in this embodiment includes a perforated silicone pad and a glass plate. The glass plate seals the through holes at both ends of the perforated silicone pad to form a sealed sample chamber. Double-sided tape is coated on the glass plate to fix the photothermal agent inside the sample chamber. It is worth noting that the material used to fix the photothermal agent includes but is not limited to double-sided tape. Other materials that can maintain viscosity to the photothermal agent particles in the solution and will not affect the heating of the photothermal agent particles can also be used in the present invention. No special limitation is made here. In the present invention, the double-sided tape can be 3M double-sided tape, model 49054910.
[0040] Step S2: Disperse the photothermal agent in pure water for micro dilution, and drop the resulting solution on the double-sided tape in the sample chamber, and wait for it to dry naturally at room temperature for use.
[0041] In the present invention, the particles used as the photothermal agent are ferroferric oxide particles, and the particle size range is 1.8-3.0 μm. The experiment requires photoheating the ferroferric oxide particles and observing the process of generating bubbles due to the evaporation of the liquid caused by the photoheating. Therefore, in order to observe the bubble generation process without interference, it is necessary to micro-dilute the high-concentration ferroferric oxide solution containing a large number of particles. The micro-dilution degree is to dilute the ferroferric oxide particles to a single digit that can be observed under a microscope, and the ferroferric oxide particles will not interfere with the bubble generation and observation.
[0042] The micro-diluted solution is dropped onto the double-sided tape in the sample chamber, and after drying, ferroferric oxide particles fixed on the double-sided tape can be obtained.
[0043] Step S3: Fill the sample chamber with pure water, use a laser with a wavelength of 1064nm to irradiate the photothermal agent particles on the surface of the double-sided adhesive tape until bubbles are generated, start timing when the bubbles begin to be generated, and take microscopic photos of the photothermal agent particles and the bubble growth process.
[0044] During the test, the sample chamber is sealed and filled with pure water so that the ferroferric oxide particles are immersed in the water. A strong penetrating laser optical tweezer with a wavelength of 1064nm is used to irradiate a single ferroferric oxide particle. The laser power range is 0.1-0.3W. Here, a laser with a power of 0.15W is used for irradiation. The ferroferric oxide particles are photographed under a microscope. When the ferroferric oxide particles evaporate the surrounding water phase due to the photothermal effect to generate bubbles, the timing starts, and the bubble growth process is continuously photographed until the bubble diameter is in a stable state. The photographing device is used to collect and process the changes in the size of the bubbles over time in the process for subsequent calculations.
[0045] Step S4: Based on the image data collected during shooting and the calculated water temperature changes, the apparent photothermal conversion efficiency f during the bubble growth process is calculated, and the apparent photothermal conversion efficiency f during the bubble growth process is fitted with the bubble diameter x data using the LogNormal model to obtain the fitted data image, and based on the fitted data image, the relationship between the photothermal conversion efficiency y and the bubble diameter x is obtained.
[0046] During the laser illumination process, the heat generated by the nanoparticles is transferred to the surrounding water, causing the water temperature to rise. Since there is no other energy dissipation, the heat generated by the particles can be considered equal to the absorbed power. At this time, the temperature rise in the water satisfies equation (1):
[0047]
[0048] For the photothermal conversion process, assuming that the bubble growth rate is constant, the power consumed by the laser during the process is P lIt can be considered that it is completely absorbed by the photothermal agent and converted into temperature rise, then P l =P abs , and the temperature increase also satisfies formula (2):
[0049]
[0050] That is, it is related to the apparent photothermal conversion efficiency f. Therefore, by substituting equation (1) into equation (2), we can obtain a set of equations for the relationship between the apparent photothermal conversion efficiency f and the diameter x, namely equation (3):
[0051]
[0052] As the bubble grows, the bubble diameter x will continue to increase, so that the apparent photothermal conversion efficiency f will also change over time. From this, the data image between the apparent photothermal conversion efficiency f and the bubble diameter x can be obtained. Then, the LogNormal model in the Origin software can be used to fit the data image to obtain a fitting curve. The data points on the fitting curve image are analyzed to obtain the relationship between the photothermal conversion efficiency y and the bubble diameter x, which satisfies formula (4):
[0053]
[0054] According to this formula, the relationship between the actual photothermal conversion efficiency y of a specific type of photothermal agent during the photothermal heating process and the time and bubble diameter x can be obtained, thereby accurately measuring the actual photothermal conversion efficiency y at each moment in the photothermal process of the photothermal agent. Compared with the conventional method of evaluating the photothermal conversion efficiency by directly measuring the absorbed power before and after the laser, less reagent is consumed, and the interference of environmental factors on the measurement is eliminated as much as possible, providing a new technical idea for accurately measuring the photothermal conversion efficiency of the photothermal agent.
[0055] A practical example based on the above method is given below to assist in understanding the specific implementation method.
[0056] Embodiment 1:
[0057] 5 μL of 5 mg / mL ferrosoferric oxide sample was dispersed in 250 mL of pure water and dropped onto a double-sided tape (3M double-sided tape, model 49054910). The double-sided tape was allowed to dry naturally, and a perforated silicone pad was adhered around the double-sided tape to prepare a sample chamber.
[0058] Water was injected using a micro-syringe, and then the ferroferric oxide particles were irradiated with a 1064nm laser. The laser power was 0.15W, and the particle size of the ferroferric oxide particles was 1.86μm. The bubble growth process over time was as follows: Figure 2As shown, it can be seen that from the start of bubble generation, the bubble diameter changes suddenly from 0ms to 26ms, and then keeps growing steadily. When the bubble diameter grows to 8.01μm, it stops growing and continues to grow after 80ms. Combining formula (1), formula (2) and formula (3), the bubble size, temperature and photothermal conversion efficiency at different times during the irradiation process are shown in Table 1:
[0059] Table 1Fe 3 O 4 (1.86μm) Bubble size, temperature and photothermal conversion efficiency when irradiated with 1064nm laser for different time periods
[0060]
[0061]
[0062] Combination Figure 2 It can be seen that when the irradiation lasts for 500ms, the laser irradiation will cause the water temperature to rise by 0.1K as a whole. Then, the apparent photosothermal conversion efficiency at 500ms is calculated to be about 43% by formula (3). The bubble diameter changes greatly in the first frame, that is, from 0ms to 26ms, and then the growth rate tends to be stable until 234ms.
[0063] The data in Table 1 were brought into the LogNormal model in the Origin software for fitting. Figure 6 By substituting the fitted curve data image shown in the figure into formula (4), the relationship between the photothermal conversion efficiency y and the bubble diameter x of the ferroferric oxide particles with a particle size of 1.86 μm during the photothermal process can be obtained, thereby obtaining the photothermal conversion efficiency y at any time during the photothermal process.
[0064] Embodiment 2:
[0065] The particle size of the ferroferric oxide particles selected was 2.25 μm, and the other experimental conditions were the same as those in Example 1. The growth process of the bubbles over time is as follows: Figure 3 As shown in Figure 2, bubbles are generated at 0ms, and the bubble diameter suddenly changes at around 30ms, after which the bubble diameter keeps growing at a nearly fixed rate until 500ms. Combining equations (1), (2) and (3), the bubble size, temperature and photothermal conversion efficiency at different times during the irradiation process are shown in Table 2:
[0066] Table 2Fe 3 O 4 (2.25μm) bubble size, temperature and photothermal conversion efficiency when irradiated with 1064nm laser for different time periods
[0067]
[0068] Combination Figure 3 It can be seen that in the time interval with a large change in bubble diameter, the change in water temperature is significantly greater than in other time intervals. The growth rate of bubble diameter between 130ms and 443ms is relatively stable, and the apparent photosothermal conversion efficiency is close. However, the bubble diameter decreases between 443ms and 494ms.
[0069] The data in Table 2 were brought into the LogNormal model in the Origin software for fitting. Figure 7 By substituting the fitted curve data image shown in the figure into formula (4), the relationship between the photothermal conversion efficiency y and the bubble diameter x of the ferroferric oxide particles with a particle size of 2.25 μm during the photothermal process can be obtained, thereby obtaining the photothermal conversion efficiency y at any time during the photothermal process.
[0070] Embodiment 3:
[0071] The particle size of the ferroferric oxide particles selected was 2.52 μm, and the other experimental conditions were the same as those in Example 1. The growth process of the bubbles over time is as follows: Figure 4 As shown in Figure 3, the bubble diameter changes suddenly between 0ms and 52ms, and then keeps growing steadily every 50ms. The bubble diameter changes slightly between 156ms and 416ms, and continues to grow after 416ms at a faster rate. Combining equations (1), (2) and (3), the bubble size, temperature and photothermal conversion efficiency at different times during the irradiation process are shown in Table 3:
[0072] Table 3Fe 3 O 4 (2.52μm) Bubble size, temperature and photothermal conversion efficiency when irradiated with 1064nm laser for different time periods
[0073]
[0074] Combination Figure 4 It can be seen that the change in bubble diameter between 0ms and 52ms is significantly greater than that in other time intervals. The diameter growth rate after 52ms is generally stable, and the apparent photosensitivity conversion efficiency also changes very little overall. Similar to the previous example, the bubble diameter also pauses at 390ms.
[0075] The data in Table 3 were brought into the LogNormal model in the Origin software for fitting. Figure 8 By substituting the fitted curve data image shown in the figure into formula (4), the relationship between the photothermal conversion efficiency y and the bubble diameter x of the ferroferric oxide particles with a particle size of 2.52 μm during the photothermal process can be obtained, thereby obtaining the photothermal conversion efficiency y at any time during the photothermal process.
[0076] Embodiment 4:
[0077] The particle size of the ferroferric oxide particles selected was 2.90 μm, and the other experimental conditions were the same as those in Example 1. The growth process of the bubbles over time is as follows: Figure 5 As shown in Figure 4, the bubble diameter changes suddenly between 26ms and 52ms, but then the bubble diameter shrinks slightly. After 520ms, the bubble diameter continues to grow steadily. Combining equations (1), (2) and (3), the bubble size, temperature and photothermal conversion efficiency at different times during the irradiation process are shown in Table 4:
[0078] Table 4Fe 3 O 4 (2.90μm) Bubble size, temperature and photothermal conversion efficiency when irradiated with 1064nm laser for different time periods
[0079]
[0080] Combination Figure 5 It can be seen that the bubble diameter changes greatly between 26ms and 52ms, but decreases between 52ms and 520ms. The bubble diameter continues to grow steadily from 520ms to 5070ms, but the growth rate gradually decreases.
[0081] The data in Table 4 were brought into the LogNormal model in the Origin software for fitting. Fig. 9 By substituting the fitted curve data image shown in the figure into formula (4), the relationship between the photothermal conversion efficiency y and the bubble diameter x of the ferroferric oxide particles with a particle size of 2.90 μm during the photothermal process can be obtained, thereby obtaining the photothermal conversion efficiency y at any time during the photothermal process.
[0082] It can be seen that the micro-photothermal conversion efficiency test calculation method in the present invention can realize the accurate measurement of the photothermal conversion efficiency of photothermal agent particles of different sizes at any time.
[0083] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the embodiments of the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for calculating the micro-photothermal conversion efficiency test, characterized in that: The following steps are involved: Step S1: placing a light-transmitting double-sided adhesive tape in a transparent sealed container composed of a glass slide and a cover glass to serve as a light-transmitting sample chamber; Step S2: Disperse the photothermal agent into pure water for micro dilution, and drop the resulting solution onto the double-sided tape in the sample chamber, and wait for it to dry naturally at room temperature for later use; Step S3: Fill the sample chamber with pure water, use a laser with a wavelength of 1064nm to irradiate the photothermal agent particles on the surface of the double-sided adhesive tape until bubbles are generated, start timing when the bubbles begin to be generated, and take microscopic photos of the photothermal agent particles and the bubble growth process; Step S4: Calculate the apparent photothermal conversion efficiency f during the bubble growth process based on the image data collected during shooting and the calculated water temperature change. Use the LogNormal model to fit the apparent photothermal conversion efficiency f during the bubble growth process with the bubble diameter x data to obtain a fitted data image. According to the fitted data image, the relationship between the photothermal conversion efficiency y and the bubble diameter x is obtained, where: The water temperature rise value ΔT satisfies the following formula: In formula (1), T is the absolute temperature, T0 is the absolute room temperature, x is the bubble diameter, which is twice the distance from the bubble edge to the particle center, C w is the thermal conductivity of water, P abs is the heat generated by the particles. Under ideal conditions, the laser energy is completely absorbed by the photothermal agent particles. abs Equal to the power consumed by the laser; The apparent photothermal conversion efficiency f satisfies the following formula: In formula (2), c w is the specific heat capacity of water, m w is the mass of the heated water, ΔT is the water temperature rise, P l Power consumption for laser; Substituting ΔT into equation (2) yields the relationship between the apparent photothermal conversion efficiency f and the bubble diameter x: The LogNormal model is used to fit the apparent photothermal conversion efficiency f and the bubble diameter x data satisfying formula (3) to obtain the fitted data image. According to the fitted data image, it is concluded that the relationship between the photothermal conversion efficiency y and the bubble diameter x satisfies the following formula: In formula (4), y 0 is the starting point of the fitted image, w is the logarithmic standard deviation, x c is the center point of the fitting image, A is the integral area of the fitting image, and x is the bubble diameter.
2. A method for calculating the micro-photothermal conversion efficiency according to claim 1, characterized in that: The sample chamber comprises a porous silica pad and glass plates respectively covering through holes at both ends of the porous silica pad, double-sided adhesive is coated on the glass plates, and the glass plates do not absorb 1064nm laser.
3. A method for calculating the micro-photothermal conversion efficiency according to claim 1, characterized in that: The photothermal agent particles are ferroferric oxide particles, and the particle size range is 1.8-3.0 μm.
4. A method for calculating the micro-photothermal conversion efficiency according to claim 1, characterized in that: The laser power ranges from 0.1 to 0.3 W.
5. A method for calculating the micro-photothermal conversion efficiency according to claim 1, characterized in that: The laser source that irradiates the photothermal agent particles is an optical tweezer.
Citation Information
Patent Citations
Rapid and effective photothermal conversion efficiency measurement method for photothermal agent
CN111366608A
Nano-bubble particle size distribution calculation method
CN112345417A